-3(x+2)+4(3x-8)=2(4x+7)+2(3x-6)

Simple and best practice solution for -3(x+2)+4(3x-8)=2(4x+7)+2(3x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x+2)+4(3x-8)=2(4x+7)+2(3x-6) equation:


Simplifying
-3(x + 2) + 4(3x + -8) = 2(4x + 7) + 2(3x + -6)

Reorder the terms:
-3(2 + x) + 4(3x + -8) = 2(4x + 7) + 2(3x + -6)
(2 * -3 + x * -3) + 4(3x + -8) = 2(4x + 7) + 2(3x + -6)
(-6 + -3x) + 4(3x + -8) = 2(4x + 7) + 2(3x + -6)

Reorder the terms:
-6 + -3x + 4(-8 + 3x) = 2(4x + 7) + 2(3x + -6)
-6 + -3x + (-8 * 4 + 3x * 4) = 2(4x + 7) + 2(3x + -6)
-6 + -3x + (-32 + 12x) = 2(4x + 7) + 2(3x + -6)

Reorder the terms:
-6 + -32 + -3x + 12x = 2(4x + 7) + 2(3x + -6)

Combine like terms: -6 + -32 = -38
-38 + -3x + 12x = 2(4x + 7) + 2(3x + -6)

Combine like terms: -3x + 12x = 9x
-38 + 9x = 2(4x + 7) + 2(3x + -6)

Reorder the terms:
-38 + 9x = 2(7 + 4x) + 2(3x + -6)
-38 + 9x = (7 * 2 + 4x * 2) + 2(3x + -6)
-38 + 9x = (14 + 8x) + 2(3x + -6)

Reorder the terms:
-38 + 9x = 14 + 8x + 2(-6 + 3x)
-38 + 9x = 14 + 8x + (-6 * 2 + 3x * 2)
-38 + 9x = 14 + 8x + (-12 + 6x)

Reorder the terms:
-38 + 9x = 14 + -12 + 8x + 6x

Combine like terms: 14 + -12 = 2
-38 + 9x = 2 + 8x + 6x

Combine like terms: 8x + 6x = 14x
-38 + 9x = 2 + 14x

Solving
-38 + 9x = 2 + 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
-38 + 9x + -14x = 2 + 14x + -14x

Combine like terms: 9x + -14x = -5x
-38 + -5x = 2 + 14x + -14x

Combine like terms: 14x + -14x = 0
-38 + -5x = 2 + 0
-38 + -5x = 2

Add '38' to each side of the equation.
-38 + 38 + -5x = 2 + 38

Combine like terms: -38 + 38 = 0
0 + -5x = 2 + 38
-5x = 2 + 38

Combine like terms: 2 + 38 = 40
-5x = 40

Divide each side by '-5'.
x = -8

Simplifying
x = -8

See similar equations:

| -55-12x=-5x+36 | | (4x+9)(x-7)= | | 2(x+4)=-5x | | 2x+4=-5x+1 | | 49n^2-81=0 | | 100=(x+2)+(x/2) | | -28=92+10x | | 100=x+2+x/2 | | 2(2w+12)=68 | | 4x-2(-1x-11)=64 | | 25a^2-80a+64=0 | | Z^2+8=4 | | a+(37+a)+(2a-40)=433 | | s-32=-29 | | 2x+8=352 | | (x)(x+1)(x+2)=36 | | 8x-(5x+4)=7+(2x-3) | | -5x+4(-3+3)=-192 | | x^2*y-3*x*y=0 | | 5(2a+4)=6a-4 | | 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 | | -x+6x-9=0 | | 2y=-10x+4 | | -7=9x+16-10 | | 2(x+p)=3(6p-x) | | 9k-3k=30 | | 3y+4=y+18 | | -44-1x=28-4x | | x-7.1=-6.2 | | -(3y+1)-(-2y-7)=2 | | 96-2x=43x+16 |

Equations solver categories